(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A clinical observation of the treatment of a patient with the consequences of spinal cord injury using non-invasive electrical stimulation of the spinal cord in combination with mechanotherapy is presented.